Analysis of the Needs for Developing E-SWS Integrated Measurement of Ethnoscience and Joyfull Learning to Facilitate Students' Creative Thinking Skills and Knowledge - Mentari Azrina Shalsabilla Shalsabilla (Department of Physics Universitas Negeri Padang, 2025)
21st-century education demands adaptive, critical, and innovative students, in line with the Independent Curriculum, which emphasizes essential competencies and the Pancasila Student Profile. However, preliminary learning at SMAN 1 2X11 Enam Lingkung revealed several obstacles in physics learning. The use of information and communication technology (ICT) in electronic Student Worksheets (E-SWS) is still low, students have difficulty understanding measurement material, low interest in reading discourse questions, and students' creative thinking skills are relatively low. This study uses descriptive statistical analysis to describe, summarize, and present data without generalization. The focus of the analysis includes frequency distribution, measures of central tendency (mean, median, mode), and measures of dispersion (range, standard deviation). The results of the analysis show that the current SWS is less attractive, is still in printed form, and does not facilitate the development of students' knowledge and creative thinking. Teacher questionnaires also indicate that they have not used electronic SWS and have not integrated ethnoscience and fun learning. Furthermore, the problem regarding the analysis of the context of SWS in real conditions with ideal conditions with an average score of 40% which is still in the low category, students' understanding of the measurement material is very low, with an average score of only 34.16%. Analysis of 31 students shows an average score of the knowledge aspect of 66.1% (mode 55, median 70, distance 100), and the creative thinking ability aspect of 55.6% (mode 50, median 55, distance 35). These data indicate that the level of knowledge and creative thinking ability of students is still low. This finding emphasizes the urgency of learning innovation to achieve the goals of the Independent Curriculum.